Pelatihan Kompetensi Guru Bahasa Arab Dalam Pemanfaatan Teknologi Digital Untuk Pembelajaran Bahasa Arab Di Pondok Pesantren Tahfidzul Quran Darul Hidayah Kemiling Bandar Lampung - Hamdal Zakariya; Hendri Jaya; Danang; Dzaki Hafidz; Gallanta Arighi (Al Mufid, 2023)
The purpose of this training is expected to provide good changes for teachers and especially Arabic teachers, thus impacting the development of students in learning Arabic. The method in this training begins with providing theories about the importance of using digital technology first, then providing opportunities for participants to ask questions and discussions about material that has been delivered and that has not been understood, then the last activity participants are assigned to make an independent argument related to the importance of digital technology in learning Arabic. This training activity ended with the practice of how to use digital technology in the Arabic learning process well. Based on the training activities that have been carried out, it can be concluded that conducting Arabic teacher competency training in the use of digital technology for Arabic language learning at the Tahfidzul Quran Darul Hidayah Kemiling Bandar Lampung Islamic boarding school is right on target and very useful.